Computer Programming Classroom Platform - Kanut Tangtisanon; Kiatnarong Tongprasert (My University, 2021)
It is widely accepted that a crucial part of learning is practicing. This is also true for computer programming courses. Students develop advanced skills and understand what they have learned better through practice. The more they practice, the more skillful they become. However, with hundreds of students in a class, an instructor may not be able to check the outcomes of student practice thoroughly nor give sufficient and timely feedback on practice to each student. An easily accessible learning platform plays an important role in dealing with this issue.Nowadays, since the internet can be accessed by anyone, a web application as a learning platform was expected to be able to play this role. Therefore, we developed a web application. It was intended for any student in any computer programming course: it was used by students in a programming course in King Mongkut's Institute of Technology Ladkrabang, Thailand, since 2017. No prior programming knowledge was required for students to use the application. The programming course had 10 chapters and one examination. In each chapter, students were required to code five programs on a PC in the programming laboratory and to submit the source files by uploading them via the web interface. The outputs of the submitted programs from all students were collected in a few seconds rather than minutes. If a submitted program was correct, proper scores were assigned. If not, the student's wrong source code was displayed on the application page together with test cases both of sample and students, and the student could examine effortlessly the incorrect part of his or her source code. Later, the student could modify the original source code and resubmit it, until the student has arrived at the correct code. This strategy was less stressful on students, because they could keep working on assignments at their own time and pace, until they were successful. Throughout the course with 789 students in the first semester of academic year 2020, the web application platform handled over 70,000 submissions of source code, beyond the capability of a human instructor. This large number of submissions indicated that the students had more time, opportunity and will to edit their source code thoroughly with this platform. Moreover, the students seemed to enjoy their attempts to overcome the programming challenge with this platform.
Keywords: Teaching and Learning Programming; Experimental Learning in Engineering; Genetics, Bioinformatics, and Biomedical Research